Surface Immobilized His-tagged Azurin as a Model Interface for the Investigation of Vectorial Electron Transfer in Biological Systems. (1st October 2015) - Casalini, Stefano; Berto, Marcello; Kovtun, Alessandro; Operamolla, Alessandra; Di Rocco, Giulia; Facci, Paolo; Liscio, Andrea; Farinola, Gianluca M.; Borsari, Marco; Bortolotti, Carlo A.
Abstract: A model system for the electrochemical investigation of vectorial electron transfer in biological systems was designed, assembled and characterized. Gold electrodes, functionalized with a -OCH3 terminated, aromatic self-assembled monolayer, were used as a substrate for the adsorption of variants of copper-containing, redox metalloprotein azurin. The engineered azurin bears a polyhistidine tag at its C-terminus. Thanks to the presence of the solvent exposed tag, which chelates Cu 2+ ions in solution, we introduced an exogenous redox centre. The different reduction potentials of the two redox centres and their positioning with respect to the surface are such that electron transfer from the exogenous copper centre and the electrode is mediated by the native azurin active site, closely paralleling electron transfer processes in naturally occurring multicentre metalloproteins.